Kritik Sosial dalam Cerpen Surat Kabar Harian Kompas Edisi Januari 2012 - Vico, Bastian Hendri; R., Syahrul; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This article was written that has purpose to describe the kind of social critic in the short story, Harian Kompas January 2012 edition, and also describe what is the cause of social critics in the short story, Harian Kompas January 2012 edition. This research used descriptive method that was a method to describe about the event in objective. This research data was consisting about the events that related with social problems in that short story. Based on the result of this research has gotten some kinds of social critics, those are: (1) a justice problem, (2) poverty problem, (3) victim, (4) the problem of modern life society, and (5) the problem about violation of society norms. There are some factors that cause of social critics, those are: (1) economic factor, and (2) psychology factor.